Occurrence of toxin genes in Staphylococcus pseudintermedius from diseased dogs and other domestic and wild species - Pitchenin, Leticia Camara; Brandão, Laila Natasha Santos; Rosa, Janaina Marcela Assunção; Kagueyama, Francielle Cristina; Alves, Alvair da Silva; Rocha, Ícaro Sergio Magalães; Nakazato, Luciano; Dutra, Valéria (The Journal of Infection in Developing Countries, 2018)
Introduction: Staphylococcus pseudintermedius is coagulase-positive species of the Staphylococcus intermedius group. It is an opportunistic pathogen that can cause infection in various parts of the body and has a zoonotic potential. Although studies on the pathogenicity and epidemiology of S. pseudintermedius are limited, it is known that this bacterium has several virulence factors, including toxins. These toxins can be classified into three main groups: pyrogenic toxins with superantigenic properties such as toxic shock syndrome toxin and staphylococcal enterotoxins, exfoliative toxins, and cytotoxins such as hemolysins and leukocidins. Methodology: In this study, the occurrence of eight toxin genes (sea, sec, tst, SIET, EXI, LuK F-I, Luk S-I, and hlg ƴ) was examined by PCR in 58 isolates of S. pseudintermedius from four domestic animal species. Results: All S. pseudintermedius isolates had at least one of the eight toxin genes. The predominant toxin genes were Luk S-I (95%), Luk F-I (91%), and EXI (91%), and the least prevalent gene was hlg ƴ (5%). Significant association (p = 0.0175) was found between the occurrence patterns of genes hlg ƴ and Luk F-I. Conclusions: The frequent occurrence of these genes in S. pseudintermedius obtained from diseased animals indicates that these toxins may play an important role in the pathogenesis of infection among domestic animals.